THE SITUATION OF CARDIOVASCULAR DISEASES IN THE ELDERLY IN VINH CITY, NGHE AN PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the common cardiovascular disease status of the elderly in Vinh city, Nghe An province, in 2024.Methods: A cross-sectional descriptive study in the community. Research subjects are elderly individuals with cardiovascular diseases living in 5 communes of Vinh City, Nghe An Province, from 7/2024 to 12/2024.Results: The rate of cardiovascular diseases in the elderly was 59%, in which hypertension was the most common cardiovascular disease, with the rate of 55,86%, followed by ischemic heart disease (19.57%), cerebrovascular disease (16.71%) and arrhythmia (9.71%); the rate of other cardiovascular diseases, such as, arterial and venous diseases, heart failure and cardiomyopathy, were 5.14%, 4.57% and 3.43%, respectively. The prevalence of cardiovascular disease differed significantly between educational and occupational groups. Specifically, the prevalence of cardiovascular disease was highest in the group of uneducated/illiterates (72.22%) and the group of self-employed older adults (71.54%).Conclusion: The study has shown that it is necessary to strengthen health education communication, raise awareness of cardiovascular diseases, and improve access to health services in the elderly, especially in groups with low education and unstable occupations.